Settlement and land use by Fulani pastoralists in case study areas - Waters-Bayer, Ann; Taylor-Powell, E. (International Livestock Centre for Africa, 1986)
Presents results of studies of settlement, land use & relations w. settled farmers of Fulani agropastoralists in Abet & Kachia Grazing Reserve in Subhumid Nigeria. Discusses reasons of choice of site, pattern & right of grazing and access to land.